Pass-by-pass stress evolution in multipass welds. (April 2014) - Gao, H.; Dutta, R. K.; Huizenga, R. M.; Amirthalingam, M.; Hermans, M. J. M.; Buslaps, T.; Richardson, I. M.
<x content-type="archive" xml:space="preserve">Abstract</x> In multipass welding, each successive thermal cycle will introduce local melting, solid state phase transformations, grain growth, grain refinement, recrystallisation and recovery, all of which lead to a complicated stress state. Most stress measurements performed on multipass welded components represent the final residual stress state. Information concerning stress evolution on a pass-by-pass basis is difficult to find. In this investigation, six pass welds were made on high strength quenched and tempered steel sections, and depth resolved strain measurements in two orthogonal directions were carried out after each weld pass using energy dispersive synchrotron X-ray diffraction. The residual stresses were calculated using biaxial Hooke's law. A thermal–metallurgical–mechanical welding model was constructed and validated with temperature and pass-by-pass stress measurements, which improves the reliability of the model. Cross-sectional stress distributions are presented after each pass, revealing the weld stress development in multipass welds.